Faktor Pendukung Dan Penghambat Bagi Mediator Dalam Melakukan Mediasi Terhadap Para Pelaku Pisah Ranjang Di Pengadilan Agama Gorontalo Kelas 1a - Nisrina M. Adam; Nur Mohamad Kasim; Dolot Alhasni Bakung (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the supporting factors, both internal and external supporting factors, and inhibiting factors, both internal and external inhibiting factors, for mediators in mediating against bed-separated perpetrators at the Class 1A Gorontalo Religious Court. This research is classified as empirical research with a case, context and sociological law approach. Data sources were obtained through interviews and observations which were then analyzed descriptively. The results of this research show that in conducting mediation, both Judge Mediator and non-Judge Mediator still experience several obstacles which have an impact on the success of the mediation process.